A Phase 2 Randomized Controlled Multisite Study Using Omalizumab-facilitated Rapid Desensitization to Test Continued vs Discontinued Dosing in Multifood Allergic Individuals - Andorf, Sandra (EClinicalMedicine, 2019)
BACKGROUND: As there is limited data on the sustainability of desensitization of multifood-oral immunotherapy (multifood-OIT), we conducted a multisite multifood-OIT study to compare the efficacy of successful desensitization with sustained dosing vs discontinued dosing after multifood-OIT. METHODS: We enrolled 70 participants, aged 5–22 years with multiple food allergies confirmed by double-blind placebo-controlled food challenges (DBPCFCs). In the open-label phase of the study, all participants received omalizumab (weeks 1–16) and multi-OIT (2–5 allergens; weeks 8–30) and eligible participants (on maintenance dose of each allergen by weeks 28–29) were randomized 1:1:1 to 1 g, 300 mg, or 0 mg arms (blinded, weeks 30–36) and then tested by food challenge at week 36. Success was defined as passing 2 g food challenge to at least 2 foods in week 36. FINDINGS: Most participants were able to reach a dose of 2 g or higher of each of 2, 3, 4, and 5 food allergens (as applicable to the participant's food allergens in OIT) in week 36 food challenges. Using an intent-to-treat analysis, we did not find evidence that a 300 mg dose was effectively different than a 1 g dose in maintaining desensitization, and both together were more effective than OIT discontinuation (0 mg dose) (85% vs 55%, P = 0.03). Fifty-five percent of the intent-to-treat participants and 69% of per protocol participants randomized to the 0 mg arm showed no objective reactivity after 6 weeks of discontinuation. Cross-desensitization was found between cashew/pistachio and walnut/pecan when only one of the foods was part of OIT. No statistically significant safety differences were found between the three arms. INTERPRETATION: These results suggest that sustained desensitization after omalizumab-facilitated multi-OIT best occurs through continued maintenance OIT dosing of either 300 mg or 1 g of each food allergen as opposed to discontinuation of multi-OIT. FUNDING: Sean N. Parker Center for Allergy and Asthma Research at Stanford University, Jeff and MacKenzie Bezos, NIAID AADCRC U19AI104209. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov number, NCT02626611.